Halal Certification and Consumer Trust: A Literature Review on the Halal Industry in Nigeria - Muhammed Thani, Taofeek (Tunas Institute, 2025)
Halal certification is expected to serve not only as a guarantee of product compliance with Islamic law but also as a mechanism to build public trust in Sharia adherence. In practice, however, its implementation in Nigeria faces persistent challenges such as institutional fragmentation, lack of standard integration, and limited resources that undermine the credibility of the certification system. This study aims to examine the role of halal certification in shaping consumer trust and to identify key factors determining the credibility of certification bodies in Nigeria. Employing a literature-based approach, this study analyzes recent research on certification governance, consumer behavior, and institutional trust. The findings reveal that halal certification functions not only as an indicator of Sharia compliance but also as a quality signal that enhances consumer loyalty. The credibility of certification bodies depends on transparency, auditor competence, moral integrity, and both regulatory and social support. These findings underscore the importance of synergy among government, religious authorities, and society in establishing a standardized, transparent, and sustainable halal certification system. The study offers a conceptual contribution to strengthening halal governance in developing countries that face institutional complexities, such as Nigeria.